SRSF3 and hnRNP A1-mediated m6A-modified circCDK14 regulates intramuscular fat deposition by acting as miR-4492-z sponge - Chunyu Qin; Fang Xu; Binglin Yue; Jincheng Zhong; Zhixin Chai; Hui Wang (Cellular & Molecular Biology Letters)
Abstract The intramuscular fat (IMF) content of yak beef is critical for determining its quality. Circular RNAs (circRNAs) are a group of endogenous non-coding RNAs that have emerged as important factors in the regulation of IMF deposition. However, the molecular mechanisms through which circRNAs regulate IMF deposition, particularly in yaks, remain unclear. In the present study, a novel circRNA, circCDK14 (originating from the yak’s CDK14 gene), was identified by sequencing and RNase R treatment. In our previous study, we successfully established a ceRNA network map and identified miR-4492-z, which interacts with circCDK14. Furthermore, using methylation prediction software, we predicted two genes, SRSF3 and hnRNP A1, that have a strong binding relationship with circCDK14; existing research has confirmed their close association with m6A methylation modifications. On the basis of these findings, we comprehensively evaluated the effects of circCDK14, miR-4492-z, SRSF3 and hnRNP A1 on the proliferation and differentiation of yak intramuscular pre-adipocytes using EdU, CCK-8, BODIPY, Oil Red O and qRT-PCR analyses. Mechanistically, the interaction between circCDK14 and miR-4492-z was validated using a dual-luciferase reporter gene assay and rescue experiments. RIP assays revealed the binding interaction of circCDK14 with SRSF3 and hnRNP A1. The MeRIP experiments showed modification of circCDK14 methylation, with SRSF3 and hnRNP A1 promoting the methylation and translocation of circCDK14 from the nucleus to the cytoplasm. In summary, our results suggest that m6A-modified circCDK14 plays a crucial role as an miR-4492-z sponge in regulating IMF deposition in yaks and that the nuclear export of circCDK14 correlates with the expression levels of SRSF3 and hnRNP A1. This study provides a theoretical basis for the improvement of yak meat quality and promotes the development of molecular yak breeding.